KUKUM Impreg Wood - Che Mohd Ruzaidi, Ghazali; Kamarudin, Hussin; Shamsul Baharin, Jamaludin; Khairul Nizar, Ismail (Malaysian Invention & Design Society (MINDS), 2010)
Che Mohd Ruzaidi Ghazali and his team won silver for KUKUM Impreg Wood.